Development and Validation of the General Learning Motivation Regulation Scale for Chinese High Middle School Students - Li, Li; Fan, Anhua (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
Motivation regulation has a profound effect on the students’ learning and associated achievement. Yet, to date, there is a lack of a brief and valid approach for systematically assessing the regulation of learning motivation from the perspective of psychometrics, especially for the high middle school students. This study develops a general scale for quantitatively assessing the learning motivation regulation of high middle students, based on the combination of literature analysis and open‑ended interviews in china General Learning Motivation Regulation Scale for Chinese High Middle School Students (GLMR‑CHMSS). A total of 2,304 questionnaires of high middle school students were included for item analysis and exploratory factor analysis, and another 2,304 questionnaires of high middle school students were subjected to confirmatory factor analyses and a validation and reliability test. The scale consisted of 24‑items that can be divided into four factors: intrinsic motivation regulation, extrinsic motivation regulation, volitional behavioural regulation, and self‑efficacy regulation. As indicated by the confirmatory factor analysis with the control group, the four‑factor structure model of the GLMR‑CHMSS fitted well (χ2 /df=7.839, RMSEA=0.054, CFI=0.918, TLI=0.908). In ad dition, using academic achievement as the empirical validity criterion, the scores of each factor of GLMR‑CHMSS and the scale score were significantly correlated with academic achievement were the reliability indicators. This study show cases a novel and valid tool for mesuring the degree of learning motivation regulation of high middle school students in China.